Educational stratification and social dynamics of regular and plus class programs at Muhammadiyah 2 Senior High School Medan - Daffa Aryabima, Andarifka (Priviet Social Sciences Journal, 2025)
Educational stratification has become increasingly evident in the Indonesian school system through the differentiation of learning programs, one of which is the division between regular and additional classes. This study examines educational stratification and social dynamics through the implementation of regular and additional class programs at Muhammadiyah 2 Senior High School Medan. The establishment of the plus class program, initiated in 2013, was largely driven by parental aspirations to provide enhanced educational facilities and differentiated learning approaches for gifted students. Although the program introduces distinctions in tuition fees, facilities, and academic expectations, its impact on students’ motivation and social interaction remains underexplored. Using a descriptive qualitative approach, data were collected through in-depth interviews with a teacher, a regular class student, and a plus class student, complemented by participatory observation and document analysis. The findings reveal that although structural differences exist between the two programs, students perceive no significant social divisions. Interactions between regular and plus-class students remain harmonious, and teachers ensure equal treatment in the learning process. The results further indicate that stratification is not primarily an institutional initiative but rather a response to parental demand. From a sociological perspective, this study demonstrates that educational stratification does not necessarily produce social inequality. Instead, it can be understood as a form of differentiation that, if managed inclusively, supports both parental expectations and institutional goals without undermining social cohesion. This study contributes to the discourse on education and stratification by highlighting how schools can manage program differentiation while promoting equity and inclusiveness.